Development of Ground Vehicle for Fire Fighting Purpose - Tan, CheeFai; Alkahari, M.R.; Abdul Rahman, M. N. (2011)
Fire fighting is risky profession. They are not only extinguishing fires in tall buildings but also must drag heavy hoses, climb high ladders and carry people from buildings and other situations. There are many fire fighters lost their lives in the line of duty each year throughout the world. The statistics of the fire fighter fatalities are still maintain at high level every year and it may continue to increase if there is no improvement in fire fighting techniques and technology. This paper describes the development of ground vehicle for fire fighting purpose.